The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41467-018-06263-5
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin swelling drives neutrophil extracellular trap release

Abstract: Neutrophilic granulocytes are able to release their own DNA as neutrophil extracellular traps (NETs) to capture and eliminate pathogens. DNA expulsion (NETosis) has also been documented for other cells and organisms, thus highlighting the evolutionary conservation of this process. Moreover, dysregulated NETosis has been implicated in many diseases, including cancer and inflammatory disorders. During NETosis, neutrophils undergo dynamic and dramatic alterations of their cellular as well as sub-cellular morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
230
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 181 publications
(260 citation statements)
references
References 70 publications
(67 reference statements)
22
230
2
6
Order By: Relevance
“…All of the above results suggest that nuclear lamin B was not destructively cleaved during NETotic nuclear envelope rupture. Therefore, our results are in line with several other studies (Amulic et al, 2017;Neubert et al, 2018) and suggest that the rupture of the nuclear envelope appears to be a distinct process from the previously described lysis or dissolution of the nuclear envelope (Fuchs et al, 2007;Papayannopoulos et al, 2010;Yipp and Kubes, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…All of the above results suggest that nuclear lamin B was not destructively cleaved during NETotic nuclear envelope rupture. Therefore, our results are in line with several other studies (Amulic et al, 2017;Neubert et al, 2018) and suggest that the rupture of the nuclear envelope appears to be a distinct process from the previously described lysis or dissolution of the nuclear envelope (Fuchs et al, 2007;Papayannopoulos et al, 2010;Yipp and Kubes, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our novel findings, a recent work from Zychlinsky and colleagues reported that cyclin dependent kinases (CDK) 4/6 might be important in the regulation of neutrophil NETosis through phosphorylation of lamin A/C (Amulic et al, 2017). In addition, Neubert et al reported that nuclear chromatin swelling provides physical driving force that causes the nuclear envelope rupture and release of neutrophil NETs (Neubert et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations